The syntax of violence - Arteaga, Juan Carlos (2019)
The present article reflects on the representation of violence in two literary and cinematic works: Los cachorros, by Mario Vargas Llosa, and Irreversible, by Gaspar Noé. It builds on the hypothesis that violence is constructed with a specific syntax that may correspond to a literary or audiovisual language. Finally, it establishes that mimesis is not only found in the description of an object but rather in its syntax, in the construction of the sentence.